Use of Patient-reported Outcome Measures (PROMs) by Orthopedic Surgeons in Saudi Arabia - Thamer Alanazi (Journal of Spine Practice)
Introduction: There is increasing literature on the usefulness of patient-reported outcome measures (PROMs), but far fewer studies to determine their use by orthopedic surgeons and the barriers they face in applying PROMs in their daily clinical activity.